Elaboración de pasas de capulí (Prunus salicifolia) por deshidratación mediante circulación de aire caliente - Leon Yuquilema, Marco Antonio (2026)
The capulí (Prunus salicifolia) is an Andean fruit with high nutritional value, but its post-harvest life is short and it has a high level of perishability, leading to significant losses and limiting its commercialization in its fresh state. Given this situation, I proposed converting the capulí into raisins through a hot-air dehydration process, with the aim of extending its shelf life, preserving its nutritional qualities, and creating an option for agro-industrial use. The research was carried out with a quantitative experimental approach and a completely randomized design, considering a temperature variable (60 °C, 70 °C, and 80 °C) and performing three replicates. The drying behavior was documented, and the physicochemical characteristics of both the fresh fruit and the raisins (moisture, protein, fat, fiber, and ash) were analyzed using AOAC (2005) techniques. The results were analyzed using analysis of variance (ANOVA), and a sensory acceptance evaluation was conducted with 96 consumers using a five-point hedonic scale. The findings revealed an inverse relationship between time and moisture content (R² > 0.98), with the 80 °C treatment for 180 minutes being the most effective, exhibiting a slope of −0.347 kg/hour and a final moisture content of 21.40 ± 0.20%, which is within the ideal range for dehydrated fruit. The process increased the concentration of nutrients: protein 7.33 ± 0.57%, fiber 3.87 ± 0.07%, fat 1.34 ± 0.04%, and ash 5.55 ± 0.09%, improving the product's nutritional density. In the sensory evaluation, the capulí raisins received a generally positive rating, with their flavor (3.45 ± 0.30/5) and texture (3.04 ± 0.50/5) being particularly noteworthy. It is concluded that dehydration at 80 °C is the optimal condition for producing capulí raisins that offer nutritional and sensory quality, presenting them as an effective option for reducing post-harvest losses and diversifying the agro-industrial offering in Ecuador.